2013
DOI: 10.1021/jp401066v
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Study of GSH and GSSG Using Constant-pH Molecular Dynamics Simulations

Abstract: Glutathione is a small peptide with a crucial role in living organisms. This molecule is found in Nature in both reduced (GSH) and oxidized (GSSG) forms and a high GSH/GSSG ratio is essential to the cell. Glutathione is also present in several enzymatic reactions and can be found in many protein structures. As small peptides, these molecules do not have a defined structure in solution and are able to sample a broad conformational space. In addition, both molecules have several titration sites (four in GSH and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 118 publications
0
40
0
Order By: Relevance
“…The percentage of the distribution of the structures on the RMSD – R gyr surface was also calculated ( Figure 2 ). In order to describe the flexibility of GSH from another structural point of view we used the same parameters as Machuqueiro et al [20]. All possible distances were measured between the Gly.OT1/OT2 and GGL.OT1/OT2/N and the minimum value among these 6 distances was used as the head-tail distance (HT).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of the distribution of the structures on the RMSD – R gyr surface was also calculated ( Figure 2 ). In order to describe the flexibility of GSH from another structural point of view we used the same parameters as Machuqueiro et al [20]. All possible distances were measured between the Gly.OT1/OT2 and GGL.OT1/OT2/N and the minimum value among these 6 distances was used as the head-tail distance (HT).…”
Section: Resultsmentioning
confidence: 99%
“…Recently Machuqueiro et al . performed constant-pH MD simulations for GSH and GSSG (oxidized form of GSH) [20]. They concluded that the conformational flexibility of GSH is pH-dependent and it has reduced flexibility at higher pH (pH>10) values.…”
Section: Introductionmentioning
confidence: 99%
“…Using the PB-based DpHMD method [12], the Baptista and Machuqueiro groups investigated the pH-dependent conformational change of the prion protein [45, 46] as well as small peptides [47]. Using the GB-based DpHMD method [14], the Roitberg group studied the pH-dependent conformational variability of the Nitrophorin proteins [48, 49].…”
Section: Recent Applications Of Constant Ph Molecular Dynamicsmentioning
confidence: 99%
“…The GSH support material and the solution pH value play an important role in the HMI-GSH complexation pattern. Research has shown that GSH's conformational structure is strongly influenced by the solution pH [38]. Various functional groups in GSH can participate in complexation under different working conditions, leading to a certain selectivity.…”
Section: Appl Sci 2018 8 X For Peer Review 3 Of 21mentioning
confidence: 99%